FACTORS INFLUENCING GENDER IMBALANCE IN SECONDARY SCHOOL LEADERSHIP IN NGOMA DISTRICT, RWANDA - MUKANKUNZI, Pélagie (IJRDO-Journal of Applied Science, 2017)
Gender inequality persists in many countries and regions of the world. In the domain ofeducation, especially in teaching and leadership, Coleman (2001: 1) and Ribbins (2008:70)confirm the dominance of men in school leadership positions. In Rwanda, the existing statisticshows that men dominate women in school leadership positions. Only 16.7% of head teachers inpublic schools are women, and men represent 83.3%. In Ngoma District, in the EasternProvince of Rwanda, men have a huge majority in leadership positions in secondary schools;among 53 head teachers, only 13 or 24.5% are women and 40 or 75.5 % are men. This studyinvestigates why women, even when they are qualified, do not apply for leadership positions inspite of a political structure that promotes women’s empowerment in Rwanda.